1999
DOI: 10.1111/j.1540-8167.1999.tb00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Limitations of Published Algorithms Using the Twelve‐Lead Electrocardiogram to Localize Overt Atrioventricular Accessory Pathways

Abstract: Our study suggests that the accuracy of algorithms relying on the 12-lead ECG depends on AP locations as defined in the algorithms and on the number of AP sites. The accuracy tends to be lower when delta wave polarity is not included in the algorithm's architecture. This should be considered when using these algorithms or when building new ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…This fact, common to the study of Wren et al., 9 was also observed in a study by Moraes et al, 10 in which the agreement rates obtained with the application of different algorithms in a sample of 190 patients with WPW syndrome proved to be substantially below those published by the authors of each algorithm (including, among others, the algorithm by Iturralde et al with an agreement rate of 54.7%). Similar findings were obtained in a study published by Basiouny et al, 23 which compared 11 algorithms applied to 266 ECGs of patients with WPW syndrome. These researchers found significantly lower results for those algorithms with more than six possible locations for the AP.…”
Section: Discussionsupporting
confidence: 85%
“…This fact, common to the study of Wren et al., 9 was also observed in a study by Moraes et al, 10 in which the agreement rates obtained with the application of different algorithms in a sample of 190 patients with WPW syndrome proved to be substantially below those published by the authors of each algorithm (including, among others, the algorithm by Iturralde et al with an agreement rate of 54.7%). Similar findings were obtained in a study published by Basiouny et al, 23 which compared 11 algorithms applied to 266 ECGs of patients with WPW syndrome. These researchers found significantly lower results for those algorithms with more than six possible locations for the AP.…”
Section: Discussionsupporting
confidence: 85%
“…Basiouny et al found significantly lower results for algorithms with more than six possible locations for the AP. 16 …”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of 11 published algorithms in 266 adult patients (mostly with left-sided accessory pathways), Basiouny et al 14 found significantly worse performance for algorithms with more than six possible accessory pathway sites. They also found that the positive predictive value ranged from 86% for left lateral pathways to 45% for right anteroseptal pathways to 23% for right posterolateral pathways.…”
Section: Discussionmentioning
confidence: 99%